Magnesium alloy surface hydrotalcite in-situ reinforced super-hydrophobic composite coating and preparation method thereof
By preparing a hydrotalcite pretreatment layer and superhydrophobic coating loaded with amino acid corrosion inhibitors on the surface of the magnesium alloy, the problem of poor corrosion resistance of the magnesium alloy is solved, and the long-term corrosion resistance and high binding force of the magnesium alloy surface is achieved.
Patent Information
- Application Number
- CN202411961022.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The poor corrosion resistance of magnesium alloys leads to their susceptibility to corrosion in humid environments, limiting their application in marine engineering, aerospace and other fields.
By preparing a hydrotalcite pretreatment layer loaded with amino acid corrosion inhibitors on the surface of the magnesium alloy, and a superhydrophobic coating is constructed on its surface to enhance the binding force between the coating and the magnesium alloy substrate, realizing active and passive collaborative corrosion protection.
It significantly improves the corrosion resistance of the surface of magnesium alloy, extends its service life, and avoids fluorine pollution and environmental pollution.
Smart Images

Figure CN119709003A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special functional materials and magnesium alloy surface anticorrosion, and in particular relates to a hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of a magnesium alloy and a preparation method thereof. Background Art
[0002] As one of the lightest metal structural materials, magnesium alloy has the advantages of light weight, high specific strength and specific stiffness, good shock absorption and impact resistance, excellent electromagnetic shielding performance, easy processing and forming, degradability, good biocompatibility, etc. It has important application value and broad application prospects in the fields of marine engineering, aerospace, national defense and military industry, automobile high-speed rail, medical implant materials, etc., and has the reputation of "green engineering materials" in the 21st century. Although magnesium alloy has a series of excellent properties, it has not been very successful in practical applications. The most important reason is the poor corrosion resistance of magnesium alloy. About 90% of the alloy components in magnesium alloy are metal magnesium. Due to the relatively low standard potential of magnesium (-2.37V), the chemical properties are very active. It is easily oxidized or corroded in humid air, marine atmosphere, seawater, most organic / inorganic acids and their salts, which causes the magnesium alloy to lose its original performance and significantly reduce its service life. Therefore, poor corrosion resistance seriously restricts the development and application of magnesium alloy.
[0003] In recent years, super-hydrophobic coatings have attracted extensive attention from researchers due to their potential applications in self-cleaning, corrosion prevention, anti-icing, anti-adhesion and other fields. Super-hydrophobic coatings refer to surfaces with a water contact angle greater than 150° and a rolling angle less than 10°. Their non-wetting properties can greatly reduce the contact area between the corrosive medium and the coating surface, greatly preventing the diffusion of corrosive ions in the electrolyte to the metal matrix, and improving the corrosiveness. However, the reported binding force between super-hydrophobic coatings and substrates is still a weak van der Waals force, and there are few reports on the binding force. Therefore, it is of great significance to design and prepare super-hydrophobic coatings with high binding force on the surface of magnesium alloys.
[0004] Gen Zhang et al. (In-situ grown super-or hydrophobic Mg-Al layered doublehydroxides films on the anodized magnesium alloy to improve corrosion properties, Surface & Coatings Technology 366 (2019) 238–247) reported that magnesium-aluminum hydrotalcite was prepared on the surface of magnesium alloy by in-situ growth method, and the surface of magnesium-aluminum hydrotalcite was modified with myristic acid and 1H, 1H, 2H, 2H perfluorodecyltrimethoxysilane to obtain a superhydrophobic coating. Characterization confirmed that this superhydrophobic coating has anti-corrosion properties. However, the article only modified the hydrotalcite layer to reduce the surface energy of the hydrotalcite. At the same time, there was no research and characterization on the mechanical properties of the superhydrophobic coating. Summary of the invention
[0005] In view of this, the present invention aims to overcome defects in the prior art, and proposes a magnesium alloy surface hydrotalcite in-situ enhanced super-hydrophobic composite coating and preparation method thereof. The present invention provides a kind of multilayer composite structure, using the hydrotalcite of load green corrosion inhibitor (amino acid) as pretreatment layer, further on the surface with nanoparticles as assembly unit to build micro-nano structure to prepare super-hydrophobic coating, by pretreatment layer and the super-hydrophobic coating of top layer chemical reaction, in-situ enhanced super-hydrophobic coating and magnesium alloy substrate bonding force, the mechanical property of coating is characterized. Meanwhile, in the preparation process, fluorine-free low surface energy material is selected to modify nanoparticles, environmentally friendly and harmless.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] In the first aspect, the present invention provides a super-hydrophobic composite coating with hydrotalcite in-situ enhanced on the surface of a magnesium alloy, wherein the super-hydrophobic composite coating comprises a magnesium-aluminum hydrotalcite pretreatment layer and a super-hydrophobic coating in-situ enhanced on the surface of the magnesium-aluminum hydrotalcite pretreatment layer, wherein the super-hydrophobic coating is prepared from components comprising a silica precursor, anhydrous ethanol, a long-chain alkoxysilane, and aqueous ammonia, wherein the volume fraction of the silica precursor in the super-hydrophobic coating is 1-5 parts, the volume fraction of the long-chain alkoxysilane is 2-10 parts, the volume fraction of anhydrous ethanol is 50-120 parts, the volume fraction of aqueous ammonia is 3-6 parts, and the long-chain alkoxysilane is an alkoxysilane having a carbon atom number of not less than 16.
[0008] In some embodiments of the present invention, the silicon dioxide precursor is one of methyl orthosilicate, ethyl orthosilicate, and butyl orthosilicate, or a mixture of two or more thereof.
[0009] In some embodiments of the present invention, the long-chain alkoxysilane is one of hexadecyltriethoxysilane, octadecyltriethoxysilane, docosyltriethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, docosyltrimethoxysilane, or a mixture of two or more thereof.
[0010] In some embodiments of the present invention, the surface of the magnesium-aluminum hydrotalcite pretreatment layer is loaded with an amino acid corrosion inhibitor.
[0011] In some embodiments of the present invention, the method for loading an amino acid corrosion inhibitor on the surface of the magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps:
[0012] The amino acid corrosion inhibitor is dissolved in deionized water to obtain a corrosion inhibitor solution with a concentration of 0.02mol / L-0.2mol / L, and the pH of the corrosion inhibitor solution is adjusted to 9-13. Then, the magnesium alloy with a magnesium-aluminum hydrotalcite pretreatment layer grown thereon is placed in the corrosion inhibitor solution, and then placed in a 40°C-80°C water bath for 18h-32h to perform intercalation loading of the corrosion inhibitor to obtain a magnesium-aluminum hydrotalcite pretreatment layer loaded with the amino acid corrosion inhibitor.
[0013] In some embodiments of the present invention, the method for preparing the magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps:
[0014] The etched magnesium alloy substrate is placed in a hydrotalcite growth solution and reacted at 100°C-140°C for 8h-16h. After the reaction is completed, the substrate is naturally cooled and the magnesium alloy substrate is taken out to obtain a magnesium-aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy.
[0015] In some embodiments of the present invention, the hydrotalcite growth liquid is an aqueous solution of aluminum nitrate with a pH value adjusted to 9-13, and the concentration of the aqueous solution of aluminum nitrate is 0.008 mol / L-0.05 mol / L.
[0016] The inventors innovatively discovered that the concentration of aluminum nitrate affects the stability of the combination between the magnesium aluminum hydrotalcite pretreatment layer and the super-hydrophobic coating. At a suitable concentration, the magnesium aluminum hydrotalcite pretreatment layer has an appropriate specific surface area and microstructure, which is conducive to constructing a micro-nano structure with a certain roughness on the surface, thereby obtaining super-hydrophobic properties. In addition, it is also conducive to the physical adsorption of the super-hydrophobic coating material, thereby improving the stability of the combination between the coating and the hydrotalcite.
[0017] In some embodiments of the present invention, the amino acid corrosion inhibitor is one or a mixture of two or more of L-glutamic acid, L-aspartic acid, and L-tryptophan.
[0018] In some embodiments of the present invention, the etching method of the magnesium alloy substrate is as follows: after polishing the magnesium alloy, ultrasonically clean it in anhydrous ethanol for 20min-60min, dry it naturally in the air after cleaning, and then put it into 4mol / L-10mol / L alkali solution for 1h-5h to achieve etching of the surface of the magnesium alloy, finally take out the magnesium alloy, clean it, and dry it with cold air to obtain the treated magnesium alloy substrate.
[0019] In a second aspect, the present invention also provides a method for preparing a hydrotalcite in-situ enhanced super-hydrophobic composite coating on a magnesium alloy surface, comprising the following steps:
[0020] S1: Take anhydrous ethanol, ammonia water and tetraethoxysilane and stir them at room temperature for 12h-18h to obtain a light blue super hydrophobic sol;
[0021] S2: After adding hexadecyltrimethoxysilane to the super-hydrophobic sol liquid prepared in step S1 and stirring at room temperature for 2-10 hours, a magnesium alloy pre-treated with a magnesium-aluminum hydrotalcite layer loaded with an amino acid corrosion inhibitor is placed therein, and reacted at 70°C-110°C for 10h-14h to obtain an in-situ hydrotalcite-enhanced super-hydrophobic composite coating on the surface of the magnesium alloy.
[0022] In some embodiments of the present invention, the method for loading an amino acid corrosion inhibitor on the surface of the magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps:
[0023] The amino acid corrosion inhibitor is dissolved in deionized water to obtain a corrosion inhibitor solution with a concentration of 0.02mol / L-0.2mol / L, and the pH of the corrosion inhibitor solution is adjusted to 9-13. Then, the magnesium alloy with a magnesium-aluminum hydrotalcite pretreatment layer grown thereon is placed in the corrosion inhibitor solution, and then placed in a 40°C-80°C water bath for 18h-32h to perform intercalation loading of the corrosion inhibitor to obtain a magnesium-aluminum hydrotalcite pretreatment layer loaded with the amino acid corrosion inhibitor.
[0024] In some embodiments of the present invention, the method for preparing the magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps:
[0025] The etched magnesium alloy substrate is placed in a hydrotalcite growth solution and reacted at 100°C-140°C for 8h-16h. After the reaction is completed, the substrate is naturally cooled and the magnesium alloy substrate is taken out to obtain a magnesium-aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy.
[0026] The present invention prepares a hydrotalcite pretreatment layer loaded with green amino acid corrosion inhibitor on the surface of the magnesium alloy, and then prepares a super hydrophobic coating on the surface, thereby giving the magnesium alloy long-term anti-corrosion performance and improving the bonding strength between the coating and the magnesium alloy. The main reasons are:
[0027] (1) The hydrotalcite in-situ enhanced super-hydrophobic composite coating can significantly reduce the contact area between the corrosive medium and the coating due to its super-hydrophobic properties, thus playing a passive anti-corrosion role for the magnesium alloy. In addition, the corrosion inhibitor loaded in the hydrotalcite pretreatment layer can react to form a new passivation film at the defect when the corrosive medium contacts the pretreatment layer after the coating is worn to form defects, thereby further isolating the contact between the corrosive medium and the magnesium alloy substrate, thereby achieving an active anti-corrosion effect.
[0028] (2) The source of magnesium in the preparation of the magnesium-aluminum hydrotalcite pretreatment layer is the magnesium alloy, so the pretreatment layer obtained by the in-situ growth method grows directly on the surface of the magnesium alloy and has a strong bonding force. The chemical reaction between the functional groups on the surface of the hydrotalcite and the silica nanoparticle building units of the super-hydrophobic coating achieves chemical bonding between the layers, thereby improving the bonding force between the super-hydrophobic coating and the magnesium alloy substrate.
[0029] In summary, through the preparation of in-situ enhanced superhydrophobic composite coating of hydrotalcite, active and passive synergistic anti-corrosion is achieved, and the bonding strength between the composite coating and the magnesium alloy substrate is greatly improved. Therefore, long-term corrosion protection of magnesium alloy can be achieved.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) The present invention prepares a double-layer composite coating on the surface of the magnesium alloy and optimizes the preparation steps of the two coatings, specifically: first, a hydrotalcite pretreatment layer is in situ grown on the surface of the magnesium alloy, and then a super-hydrophobic coating with silicon dioxide nanoparticles as building units is grown on the surface of the hydrotalcite pretreatment layer, thereby giving the magnesium alloy excellent active and passive synergistic anti-corrosion properties and self-cleaning properties, thereby achieving long-term corrosion protection of the magnesium alloy;
[0032] (2) When designing a double-layer coating system, the present invention adds a hydrotalcite pretreatment layer to react chemically with the surface super-hydrophobic coating to achieve a strong bonding force between the coating and the magnesium alloy substrate in the form of a chemical bond;
[0033] (3) In the preparation of the hydrotalcite pretreatment layer, the present invention uses a green and environmentally friendly amino acid corrosion inhibitor as an inserted hydrotalcite layer, avoiding the low toxicity and environmental pollution of the inorganic corrosion inhibitor;
[0034] (4) When preparing the super-hydrophobic coating, the present invention uses green, fluorine-free hexadecyltrimethoxysilane as a low surface energy material to reduce the surface energy of the coating and overcome fluorine pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope photograph of the hydrotalcite in-situ enhanced super-hydrophobic composite coating prepared in Example 1 of the present invention;
[0036] Figure 2 The water contact angle and rolling angle of the hydrotalcite in-situ enhanced super-hydrophobic composite coating prepared in Example 1 of the present invention;
[0037] Figure 3 The Tafel curves of the coatings prepared in Examples and Comparative Examples are shown in FIG. DETAILED DESCRIPTION
[0038] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0039] Unless defined otherwise herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0040] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0041] In this document, "multiple" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0042] In this document, the terms “preferred” and “more preferred” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present invention.
[0043] In this document, the words "further" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0044] In this article, the term "and / or" is a description of the association relationship of objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or A and B.
[0045] As used herein, the term "about" means + / - 10%, preferably + / - 5%, more preferably + / - 1% of the specified value.
[0046] The terms “include,” “including,” “have,” “contain,” etc. used in this article are open-ended terms, meaning including but not limited to.
[0047] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0048] The present invention will be described in detail below with reference to the embodiments.
[0049] Example 1
[0050] (1) Prepare AZ31B magnesium alloy, clean and etch the magnesium alloy, the specific method is as follows:
[0051] The magnesium alloy was cut into a size of 7 cm in length and 2.5 cm in width, and then polished with 400 mesh, 800 mesh, 1200 mesh and 1500 mesh sandpaper in turn, and then ultrasonically cleaned in anhydrous ethanol for 20 minutes. After cleaning, it was naturally dried in the air, and then placed in 4 mol / L alkali solution for 1 hour to achieve etching of the magnesium alloy surface. Finally, the magnesium alloy was taken out for cleaning and cold air drying to obtain the treated magnesium alloy substrate.
[0052] (2) The specific method for preparing a hydrotalcite pretreatment layer loaded with a green corrosion inhibitor (amino acid) on the surface of the etched magnesium alloy is as follows:
[0053] Raw materials: aluminum nitrate nonahydrate, L-glutamic acid corrosion inhibitor, sodium hydroxide, deionized water.
[0054] First, prepare the hydrotalcite growth solution, add 0.8 grams of aluminum nitrate nonahydrate to 105 milliliters of deionized water, stir for 10 minutes to completely dissolve the aluminum nitrate nonahydrate, and slowly add an appropriate amount of 0.5 mol / L sodium hydroxide aqueous solution to make the pH of the solution reach 9. Then, pour the mixed solution into the reactor, and further vertically place the magnesium alloy substrate etched in the first step into the solution of the reactor. Finally, place the reactor in an oven at 100 degrees Celsius and react for 8 hours. After the reaction is completed, take out the magnesium alloy from the reactor after it cools naturally, and you can get the magnesium aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy. Furthermore, an appropriate amount of amino acid corrosion inhibitor is dissolved in deionized water to prepare a corrosion inhibitor solution with a concentration of 0.02 mol / L, and the corrosion inhibitor solution is adjusted to a pH of 9 with 1 mol / L sodium hydroxide solution, and then the magnesium alloy grown with magnesium aluminum hydrotalcite obtained above is placed in the solution, and then placed in a 40 degree Celsius water bath for 18 hours to carry out intercalation loading of the corrosion inhibitor, so as to obtain a magnesium aluminum hydrotalcite pretreatment layer with amino acid corrosion inhibitor loaded on the surface of the magnesium alloy.
[0055] (3) The specific method for preparing an environmentally friendly green super-hydrophobic coating on the surface of the magnesium-aluminum hydrotalcite pretreatment layer is as follows:
[0056] Raw materials: tetraethoxysilane, anhydrous ethanol, hexadecyltrimethoxysilane, ammonia water.
[0057] Prepare super-hydrophobic coating using chemical deposition method, first prepare super-hydrophobic sol liquid, weigh 50 milliliters of absolute ethanol, 3 milliliters of ammonia, 1 milliliter of tetraethoxysilane and be placed in a conical flask, stir 12 hours at room temperature, obtain light blue sol liquid.Then, add 2 milliliters of hexadecyltrimethoxysilane thereto, continue to stir 2 hours at room temperature, you can obtain super-hydrophobic sol liquid.Super-hydrophobic sol liquid is placed in reactor, there is the magnesium alloy of the magnesium aluminum hydrotalcite pretreatment layer of load amino acid corrosion inhibitor vertically placed therein, react 10 hours at 70 degrees Celsius, you can obtain magnesium alloy surface hydrotalcite in situ enhanced super-hydrophobic composite coating.
[0058] The scanning electron microscope photo of the hydrotalcite in-situ enhanced super-hydrophobic composite coating prepared in Example 1 is shown in FIG. Figure 1 shown.
[0059] Example 2
[0060] (1) Prepare AZ31B magnesium alloy, clean and etch the magnesium alloy, the specific method is as follows:
[0061] The magnesium alloy was cut into a size of 7 cm in length and 2.5 cm in width, and then polished with 400 mesh, 800 mesh, 1200 mesh and 1500 mesh sandpaper in turn, and then ultrasonically cleaned in anhydrous ethanol for 60 minutes. After cleaning, it was naturally dried in the air, and then placed in 6 mol / L alkali solution for 3 hours to achieve etching of the magnesium alloy surface. Finally, the magnesium alloy was taken out for cleaning and cold air drying to obtain the treated magnesium alloy substrate.
[0062] (2) The specific method for preparing a hydrotalcite pretreatment layer loaded with a green corrosion inhibitor (amino acid) on the surface of the etched magnesium alloy is as follows:
[0063] Raw materials: aluminum nitrate nonahydrate, L-glutamic acid corrosion inhibitor, sodium hydroxide, deionized water.
[0064] First, prepare the hydrotalcite growth solution, add 0.8 grams of aluminum nitrate nonahydrate to 265 milliliters of deionized water, stir for 30 minutes to completely dissolve the aluminum nitrate nonahydrate, and slowly add an appropriate amount of 5 mol / L sodium hydroxide aqueous solution to make the pH of the solution reach 13. Then, pour the mixed solution into the reactor, and further vertically place the magnesium alloy substrate etched in the first step into the solution of the reactor. Finally, place the reactor in an oven at 140 degrees Celsius and react for 16 hours. After the reaction is completed, take out the magnesium alloy from the reactor after it cools naturally, and you can get the magnesium aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy. Furthermore, an appropriate amount of amino acid corrosion inhibitor is dissolved in deionized water to prepare a corrosion inhibitor solution with a concentration of 0.2 mol / L, and the corrosion inhibitor solution is adjusted to a pH of 13 with a 5 mol / L sodium hydroxide solution. Then, the magnesium alloy grown with magnesium-aluminum hydrotalcite obtained above is placed in the solution, and then placed in a water bath at 80 degrees Celsius for 32 hours to perform intercalation loading of the corrosion inhibitor, so as to obtain a magnesium-aluminum hydrotalcite pretreatment layer with amino acid corrosion inhibitor loaded on the surface of the magnesium alloy.
[0065] (3) The specific method for preparing an environmentally friendly green super-hydrophobic coating on the surface of the magnesium-aluminum hydrotalcite pretreatment layer is as follows:
[0066] Raw materials: methyl orthosilicate, anhydrous ethanol, octadecyltrimethoxysilane, ammonia water.
[0067] Preparation super-hydrophobic coating adopts chemical deposition method, first prepares super-hydrophobic sol liquid, weighs 120 milliliters of absolute ethanol, 6 milliliters of ammonia, 5 milliliters of methyl orthosilicate and is placed in a conical flask, and is stirred for 18 hours at normal temperatures to obtain light blue sol liquid.Then, 10 milliliters of octadecyl trimethoxy silane are added thereto, continue to stir 10 hours at normal temperatures, and super-hydrophobic sol liquid can be obtained.Super-hydrophobic sol liquid is placed in reactor, and the magnesium alloy of the magnesium aluminum hydrotalcite pretreatment layer with load amino acid corrosion inhibitor is vertically placed therein, and reacts 14 hours at 110 degrees Celsius, and the surface of magnesium alloy hydrotalcite in situ enhanced super-hydrophobic composite coating can be obtained.
[0068] Example 3
[0069] (1) Prepare AZ31B magnesium alloy, clean and etch the magnesium alloy, the specific method is as follows:
[0070] The magnesium alloy was cut into a size of 7 cm in length and 2.5 cm in width, and then polished with 400 mesh, 800 mesh, 1200 mesh and 1500 mesh sandpaper in turn, and then ultrasonically cleaned in anhydrous ethanol for 60 minutes. After cleaning, it was naturally dried in the air, and then placed in 10 mol / L alkali solution for 5 hours to achieve etching of the magnesium alloy surface. Finally, the magnesium alloy was taken out for cleaning and cold air drying to obtain the treated magnesium alloy substrate.
[0071] (2) The specific method for preparing a hydrotalcite pretreatment layer loaded with a green corrosion inhibitor (amino acid) on the surface of the etched magnesium alloy is as follows:
[0072] Raw materials: aluminum nitrate nonahydrate, L-glutamic acid corrosion inhibitor, sodium hydroxide, deionized water.
[0073] First, prepare the hydrotalcite growth solution, add 2 grams of aluminum nitrate nonahydrate to 105 milliliters of deionized water, stir for 20 minutes to completely dissolve the aluminum nitrate nonahydrate, and slowly add an appropriate amount of 2.5 mol / L sodium hydroxide aqueous solution to make the pH of the solution reach 13. Then, pour the mixed solution into the reactor, and further vertically place the magnesium alloy substrate etched in the first step into the solution of the reactor. Finally, place the reactor in an oven at 120 degrees Celsius and react for 12 hours. After the reaction is completed, take out the magnesium alloy from the reactor after it cools naturally, and you can get the magnesium aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy. Furthermore, an appropriate amount of amino acid corrosion inhibitor is dissolved in deionized water to prepare a corrosion inhibitor solution with a concentration of 0.1 mol / L, and the corrosion inhibitor solution is adjusted to a pH of 10 with a 3 mol / L sodium hydroxide solution. Then, the magnesium alloy grown with magnesium aluminum hydrotalcite obtained above is placed in the solution, and then placed in a 55°C water bath for 24 hours to perform intercalation loading of the corrosion inhibitor, thereby obtaining a magnesium aluminum hydrotalcite pretreatment layer with amino acid corrosion inhibitor loaded on the surface of the magnesium alloy.
[0074] (3) The specific method for preparing an environmentally friendly green super-hydrophobic coating on the surface of the magnesium-aluminum hydrotalcite pretreatment layer is as follows:
[0075] Raw materials: butyl orthosilicate, anhydrous ethanol, triethoxydibenzoylsilane, ammonia water.
[0076] Preparation super-hydrophobic coating adopts chemical deposition method, first prepares super-hydrophobic sol liquid, weighs 100 milliliters of absolute ethanol, 4 milliliters of ammonia, 3 milliliters of butyl orthosilicate alkane and is placed in a conical flask, and is stirred for 15 hours at normal temperatures to obtain light blue sol liquid.Then, 5 milliliters of dioctyl triethoxysilane are added thereto, continue to stir for 8 hours at normal temperatures, and super-hydrophobic sol liquid can be obtained.Super-hydrophobic sol liquid is placed in reactor, and the magnesium alloy of the magnesium aluminum hydrotalcite pretreatment layer with load amino acid corrosion inhibitor is vertically placed therein, and reacts 12 hours at 90 degrees Celsius, and the surface of magnesium alloy hydrotalcite in-situ enhanced super-hydrophobic composite coating can be obtained.
[0077] Comparative Example 1: Spraying super-hydrophobic coating on magnesium alloy substrate
[0078] Compared with Example 1, Comparative Example 1 is to prepare a super hydrophobic coating directly on the surface of the etched magnesium alloy by spraying, without a hydrotalcite pretreatment layer. Among them, the cleaning and etching of the magnesium alloy are the same as in Example 1, and the preparation method of the super hydrophobic sol solution is also the same as step (3) of Example 1. The difference is that the coating is prepared directly on the surface of the etched magnesium alloy by spraying, and the specific method is as follows:
[0079] The prepared super-hydrophobic sol liquid was evenly sprayed onto the etched magnesium alloy surface using an air compressor. The spraying pressure used during spraying was 40 psi and the spraying distance was 15 cm. Finally, the sprayed magnesium alloy was dried at room temperature to obtain a super-hydrophobic coating.
[0080] Comparative Example 2: Magnesium alloy substrate sprayed with hydrotalcite to enhance super-hydrophobic coating
[0081] Compared with Example 1, Comparative Example 2 is to prepare a hydrotalcite coating by spraying on the surface of the magnesium alloy, and then prepare a super-hydrophobic coating on the surface of the hydrotalcite by chemical deposition. Among them, the cleaning and etching of the magnesium alloy are the same as in Example 1, and the method for preparing the super-hydrophobic coating by surface chemical deposition is also the same as in Example 1, except that the in-situ grown hydrotalcite layer in Example 1 is replaced by a sprayed hydrotalcite layer, and the subsequent corrosion inhibitor loading is also the same as in Example 1. The specific preparation method is as follows:
[0082] Raw materials: magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, deionized water, sodium hydroxide.
[0083] First, a magnesium aluminum hydrotalcite solution is prepared, and then a magnesium aluminum hydrotalcite coating is prepared on the etched magnesium alloy surface by spraying. 100 ml of 0.5 mol / L magnesium nitrate hexahydrate and 0.25 mol / L aluminum nitrate nonahydrate are mixed together in a round-bottom flask, and then 2 mol / L sodium hydroxide solution is slowly added dropwise to adjust the pH of the mixed solution to about 10. In order to avoid the introduction of carbon dioxide, nitrogen is continuously passed into the solution. After the addition is completed, the mixed suspension is aged in a water bath at 65°C for 24 hours to obtain a magnesium aluminum hydrotalcite suspension. Further spraying is performed on the etched magnesium alloy surface, and the spraying conditions are a pressure of 40 psi and a spraying distance of 15 cm, and the magnesium aluminum hydrotalcite suspension is evenly sprayed onto the substrate surface.
[0084] Subsequently, the corrosion inhibitor loading and the surface super-hydrophobic coating were prepared by the same method as in Example 1.
[0085] Comparative Example 3
[0086] Compared with Example 1, Comparative Example 3 is to prepare an in-situ enhanced super-hydrophobic coating of hydrotalcite without corrosion inhibitor intercalation on the surface of a magnesium alloy, that is, step (1) and step (3) are the same as in Example 1, and the specific method of step (2) is:
[0087] Raw materials: aluminum nitrate nonahydrate, sodium hydroxide, deionized water.
[0088] First, prepare the hydrotalcite growth solution, add 0.8 grams of aluminum nitrate nonahydrate to 105 milliliters of deionized water, stir for 10 minutes to completely dissolve the aluminum nitrate nonahydrate, and slowly add an appropriate amount of 0.5 mol / L sodium hydroxide aqueous solution to make the pH of the solution reach 9. Then, pour the mixed solution into the reactor, and further vertically place the magnesium alloy substrate etched in the first step into the solution of the reactor. Finally, place the reactor in an oven at 100 degrees Celsius and react for 8 hours. After the reaction is completed, take out the magnesium alloy from the reactor after it cools naturally, and you can get the magnesium aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy.
[0089] Comparative Example 4
[0090] Compared with Example 1, hexadecyltrimethoxysilane was replaced by dodecyltrimethoxysilane in Comparative Example 4. Other steps were the same as those in Example 1.
[0091] Comparative Example 5
[0092] Compared with Example 1, in step (2) of Comparative Example 5, 2 g of aluminum nitrate nonahydrate was added to 80 ml of deionized water.
[0093] Performance Test:
[0094] 1. Morphology analysis:
[0095] The surface morphology of the composite coating was observed by scanning electron microscopy. The surface morphology of the super-hydrophobic composite coating reinforced with hydrotalcite on the surface of the magnesium alloy prepared in Example 1 was as follows: Figure 1 As shown in the figure, it can be seen that the flaky ones are hydrotalcite flakes, and silicon dioxide nanoparticles are deposited on the surface of the hydrotalcite, forming a double-layer composite system.
[0096] 2. Wettability characterization:
[0097] The water contact angle and the rolling angle of the prepared coating were characterized by using an optical contact angle tester. Table 1 shows the water contact angle and the rolling angle of the embodiment and the comparative example. Figure 2 The water contact angle and sliding angle of the hydrotalcite in-situ enhanced super-hydrophobic composite coating prepared in Example 1.
[0098] Table 1 Water contact angle and rolling angle of hydrotalcite in-situ enhanced super-hydrophobic composite coating prepared in Examples and Comparative Examples
[0099] sample Water contact angle Roll Angle Example 1 153° 6° Comparative Example 1 152° 5° Comparative Example 2 56° —Water drops cannot roll Comparative Example 3 152° 5° Comparative Example 4 143° —Water drops cannot roll Comparative Example 5 138° —Water drops cannot roll
[0100] 3. Characterization of anti-corrosion performance;
[0101] The Tafel curve test was performed on the treated magnesium alloy substrates in Comparative Examples 1 to 5 and the hydrotalcite in-situ enhanced super-hydrophobic composite coating obtained in Example 1 by an electrochemical method. Figure 3 As shown. Generally speaking, a lower corrosion current and a higher corrosion potential indicate that the coating has a stronger anti-corrosion performance. As can be seen from the figure, the super-hydrophobic composite coating (Example 1) enhanced by hydrotalcite in situ on the surface of the magnesium alloy has a low corrosion current and a high corrosion potential, indicating that the composite coating prepared in Example 1 has the best anti-corrosion performance.
[0102] 4. Mechanical properties characterization:
[0103] The hardness of the paint film was determined according to the national standard GB / T 6739-2022 Paints and Varnishes - Pencil Method, and a standardized pencil was used to test the paint film according to the standard procedure using a pencil hardness tester that meets the standard requirements. Table 2 shows the pencil hardness grades of the embodiments and comparative examples. The hardness grades are usually HB, B, 3H, etc., where H represents hardness and B represents blackness. The larger the number, the more obvious the corresponding characteristics. The higher the pencil hardness, the greater the hardness of the paint film, indicating that the bonding between the coating and the substrate is stronger.
[0104] Table 2 Binding strength between the coatings prepared in the examples and comparative examples and the magnesium alloy substrate
[0105] sample Pencil hardness Example 1 4H Comparative Example 1 1H Comparative Example 2 3H Comparative Example 3 4H Comparative Example 4 4H Comparative Example 5 1H
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A super-hydrophobic composite coating reinforced by hydrotalcite in situ on the surface of a magnesium alloy, characterized in that: The super-hydrophobic composite coating comprises a magnesium-aluminum hydrotalcite pretreatment layer and a super-hydrophobic coating in situ enhanced on the surface of the magnesium-aluminum hydrotalcite pretreatment layer, wherein the super-hydrophobic coating is prepared from components comprising a silica precursor, anhydrous ethanol, a long-chain alkoxysilane, and aqueous ammonia, wherein the volume fraction of the silica precursor in the super-hydrophobic coating is 1-5 parts, the volume fraction of the long-chain alkoxysilane is 2-10 parts, the volume fraction of anhydrous ethanol is 50-120 parts, the volume fraction of aqueous ammonia is 3-6 parts, and the long-chain alkoxysilane is an alkoxysilane having a carbon atom number of not less than 16.
2. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The silicon dioxide precursor is one of methyl orthosilicate, ethyl orthosilicate and butyl orthosilicate, or a mixture of two or more thereof.
3. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The long-chain alkoxysilane is one of hexadecyltriethoxysilane, octadecyltriethoxysilane, docosyltriethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, docosyltrimethoxysilane, or a mixture of two or more thereof.
4. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The surface of the magnesium-aluminum hydrotalcite pretreatment layer is loaded with an amino acid corrosion inhibitor; preferably, the amino acid corrosion inhibitor is one or a mixture of two or more of L-glutamic acid, L-aspartic acid, and L-tryptophan.
5. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The method for loading an amino acid corrosion inhibitor on the surface of a magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps: The amino acid corrosion inhibitor is dissolved in deionized water to obtain a corrosion inhibitor solution with a concentration of 0.02mol / L-0.2mol / L, and the pH of the corrosion inhibitor solution is adjusted to 9-13. Then, the magnesium alloy with a magnesium-aluminum hydrotalcite pretreatment layer grown thereon is placed in the corrosion inhibitor solution, and then placed in a 40°C-80°C water bath for 18h-32h to perform intercalation loading of the corrosion inhibitor to obtain a magnesium-aluminum hydrotalcite pretreatment layer loaded with the amino acid corrosion inhibitor.
6. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The preparation method of the magnesium aluminum hydrotalcite pretreatment layer comprises the following steps: The etched magnesium alloy substrate is placed in a hydrotalcite growth solution and reacted at 100°C-140°C for 8h-16h. After the reaction is completed, the substrate is naturally cooled and the magnesium alloy substrate is taken out to obtain a magnesium-aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy.
7. The hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 1, characterized in that: The hydrotalcite growth liquid is an aluminum nitrate aqueous solution with a pH value adjusted to 9-13, and the concentration of the aluminum nitrate aqueous solution is 0.008 mol / L-0.05 mol / L.
8. The method for preparing the hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to any one of claims 1 to 7, characterized in that: The steps include: S1: Take anhydrous ethanol, ammonia water and tetraethoxysilane and stir them at room temperature for 12h-18h to obtain a light blue super hydrophobic sol; S2: After adding hexadecyltrimethoxysilane to the super-hydrophobic sol liquid prepared in step S1 and stirring at room temperature for 2-10 hours, a magnesium alloy pre-treated with a magnesium-aluminum hydrotalcite layer loaded with an amino acid corrosion inhibitor is placed therein, and reacted at 70°C-110°C for 10h-14h to obtain an in-situ hydrotalcite-enhanced super-hydrophobic composite coating on the surface of the magnesium alloy.
9. The method for preparing the in-situ hydrotalcite-enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 8, characterized in that: The method for loading an amino acid corrosion inhibitor on the surface of a magnesium-aluminum hydrotalcite pretreatment layer comprises the following steps: The amino acid corrosion inhibitor is dissolved in deionized water to obtain a corrosion inhibitor solution with a concentration of 0.02mol / L-0.2mol / L, and the pH of the corrosion inhibitor solution is adjusted to 9-13. Then, the magnesium alloy with a magnesium-aluminum hydrotalcite pretreatment layer grown thereon is placed in the corrosion inhibitor solution, and then placed in a 40°C-80°C water bath for 18h-32h to perform intercalation loading of the corrosion inhibitor to obtain a magnesium-aluminum hydrotalcite pretreatment layer loaded with the amino acid corrosion inhibitor.
10. The method for preparing the hydrotalcite in-situ enhanced super-hydrophobic composite coating on the surface of magnesium alloy according to claim 8, characterized in that: The preparation method of the magnesium aluminum hydrotalcite pretreatment layer comprises the following steps: The etched magnesium alloy substrate is placed in a hydrotalcite growth solution and reacted at 100°C-140°C for 8h-16h. After the reaction is completed, the substrate is naturally cooled and the magnesium alloy substrate is taken out to obtain a magnesium-aluminum hydrotalcite pretreatment layer grown in situ on the surface of the magnesium alloy.
Citation Information
Patent Citations
Method for preparing super-hydrophobic film with hybrid multi-stage structure on metal matrix
CN103182369A
Method for preparation of superhydrophobic timber on the basis of sol-gel method
CN105599077A
Method for preparing glutamate intercalation hydrotalcite medicinal magnesium alloy coating
CN106693044A
Preparation method of silane-cerium oxide-hydrotalcite composite coating on surface of magnesium / magnesium alloy matrix
CN107059005A